Expert Answers

An illustration of the letter 'A' in a speech bubbles


The inverse function `g^(-1)(y)` is a function such that `g(g^(-1)(y))` = y and `g^(-1)(g(x)) = x.` To find it, we need to solve for x the equation

`g(x) = y,` in this case it is `-2x+4 = y.`

It is simple: `-2x = y-4,`  `2x = -y+4,`  `x = -1/2 y + 2.` You can check the above equalities from the definition of an inverse function.

The answer: the inverse function is `g^(-1)(y) = -1/2 y + 2.`

Approved by eNotes Editorial Team

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial